To want, to be able and to know how to speak: that is the question! (Journal of Parents and Teachers, 1996)
Didactic topics address the importance of oral expression and reality in language learning, highlighting the influence of family, school and society. The difference between the act of saying and speaking is emphasized, as well as the need to want, be able and know how to communicate effectively. In addition, the relevance of experiences and context in the development of language skills is mentioned.
Keywords: oral expression; language; effective communication; family influence